A Method for Custom-Contoured Cushion Fabrication Based on Pressure Mapping for Wheelchair Users to Prevent Pressure Ulcers: Feasibility Quasi-Experimental Study - Alma De León-Hernández; Adriana Martínez-Hernández; Isabel Bolivar-Tellería; Andrea Bosch-Sánchez; María Fernanda Cabrera-Padilla; Carlos Omar López-López (JMIR Rehabilitation and Assistive Technologies)
Abstract BackgroundPressure ulcers constitute a major health care burden, characterized by significant morbidity, diminished quality of life, and elevated treatment costs. Wheelchair users are predisposed to pressure ulcers due to sustained ischial and sacral interface pressures resulting from prolonged periods of sitting. Implementation of pressure-relieving interventions, including specialized seating systems engineered to redistribute load and augment the weight-bearing surface area, is critical for mitigating the risk of pressure ulcers. ObjectiveThis study aimed to evaluate a methodology for the custom fabrication of pressure relief cushions, through the user-cushion interface pressure mapping to reduce high-pressure areas and increase contact area in wheelchair users. MethodsFirst, a validation study was carried out with 7 healthy volunteers. The pressure was determined with an FSA sensor (BodiTrak BT1510, Vista Medical Manufactures), and the cushion profile was obtained through a linear relation with pressure values. In the second phase, 10 cushions for wheelchair users were manufactured and tested. The resulting data from buttock pressure using a flat foam, Jay ResultsIn the validation study, the statistically significant difference between the flat and the custom-contoured cushion showed a better performance in pressure relief for the custom cushion (mean pressure 27.3, SD 4.5 mm Hg and 34.6, SD 3.5 mm Hg; PP2PP ConclusionsThe main finding is that the buttock pressure mapping method produces custom-contoured cushions that, compared with commercial cushions, have good pressure distribution and increased contact area. These results suggest that pressure mapping is a good alternative for manufacturing affordable custom-contoured cushions that can prevent the development of pressure ulcers.